Analysis of land suitability, carrying capacity, and development strategies for seaweed cultivation in Labakkang District, Pangkep Regency, Indonesia - Mosriula Mosriula (Akuatikisle: Jurnal Akuakultur, Pesisir dan Pulau-Pulau Kecil, 2019)
Analysis of land, its carrying capacity and development strategy of seaweed cultivation in Labakkang, Pangkajene Regency. This study attempts to: (1) analyze the suitability of coastal land that appropriate for seaweed cultivation, (2) determine the carrying capacity of the land for seaweed cultivation, (3) formulate strategies and policies that appropriate for seaweed cultivation. This study used biophysical field survey to assess the region, analyze the suitability of the land as well as the carrying capacity of the area by using a geographic information system. Furthermore, the research analyzed the strategy and policy of development of seaweed cultivation with A'WOT analysis approach. The results of the evaluation of the suitability of land for seaweed cultivation in coastal areas showed that Labakkang has potential approximately 1632.876 ha. The area is suitable for seaweed cultivation activities around 1035.54 ha, and unsuitable area around 597.336 ha. For carrying capacity of seaweed cultivation in the coastal area of Labakkang is for 40.55 units. The priority development strategy of seaweed cultivation is strengthening institutions to make a sustainable seaweed cultivation in Labakkang.